A Comparison of the Effects of Packaging Containing Nano ZnO or Polylysine on the Microbial Purity and Texture of Cod (Gadus morhua) Fillets - Małgorzata Mizielińska; Urszula Kowalska; Michał Jarosz; Patrycja Sumińska (Nanomaterials, 2018)
Portions of fresh Baltic cod fillets were packed into cellulose boxes (control samples), which were covered with Methyl Hydroxypropyl Celluloses (MHPC) coating with 2% polylysine. The cellulose boxes had square PE films and were enclosed in MHPC coating containing ZnO nanoparticles. The cod fillets were stored at 5 °C and examined after 72 h and 144 h storage times. Results obtained in this study showed that the textural parameters of the cod fillets increased, with both Springiness and Cohesiveness found greater after 144 h of storage for all analysed packaging materials. The Gumminess of fillets increased after storage, but the lowest increase was noted in cod samples that were stored in boxes containing PE films with ZnO nanoparticles. It was found that water loss from the cod fillets in these boxes was also lowest. The Adhesiveness of the fish samples stored in boxes devoid of active coatings also increased. In contrast to the packaging material devoid of active coatings, the storage of fillets in active coating boxes resulted in a decrease of adhesiveness. Microbial analysis showed that packaging material containing nano-ZnO was found to be more active against mesophilic and psychotropic bacterial cells than the coatings with polylysine after 72 h and 144 h of storage.